Hydrophobin as a Nanolayer Primer That Enables the Fluorinated Coating of Poorly Reactive Polymer Surfaces. Issue 14 (28th July 2015) - Gazzera, Lara; Corti, Claudio; Pirrie, Lisa; Paananen, Arja; Monfredini, Alessandro; Cavallo, Gabriella; Bettini, Simona; Giancane, Gabriele; Valli, Ludovico; Linder, Markus B.; Resnati, Giuseppe; Milani, Roberto; et al.
<x xml:space="preserve">Abstract</x> A new and simple method is presented to fluorinate the surfaces of poorly reactive hydrophobic polymers in a more environmentally friendly way using the protein hydrophobin (HFBII) as a nanosized primer layer. In particular, HFBII, via electrostatic interactions, enables the otherwise inefficient binding of a phosphate‐terminated perfluoropolyether onto polystyrene, polypropylene, and low‐density polyethylene surfaces. The binding between HFBII and the perfluoropolyether depends significantly on the environmental pH, reaching the maximum stability at pH 4. Upon treatment, the polymeric surfaces mostly retain their hydrophobic character but also acquire remarkable oil repellency, which is not observed in the absence of the protein primer. The functionalization proceeds rapidly and spontaneously at room temperature in aqueous solutions without requiring energy‐intensive procedures, such as plasma or irradiation treatments.